Cellular Automata on GIS Method for Forest Fire Spreading Simulation - Arai, Kohei (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
A method for prediction and simulation based on the Cell Based Geographic Information System (CBGIS) as Cellular Automata (CA) is proposed together with required data system systems, in particular metasearch engine usage in a unified way. It is confirmed that the proposed CBGIS as CA has flexible usage of the attribute information that is attached to the cell in concern with location information and does work for disaster of forest fire spreading simulation and prediction.